BS EN ISO 16486-2. Plastics piping systems for the supply of gaseous fuels. Unplasticized polyamide (PA-U) piping systems with fusion jointing and mechanical jointing. Part 2. Pipes (28th October 2019) - British Standards Institution,
No abstract available